Pengukuran Senjangan Anggaran: Aspek Kejelasan Sasaran, Pengendalian Internal, dan Komitmen Organisasi - Putri, Aprilia Kartika; Muslimin, Muslimin; Widodo, Ulfa (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
This research aims to test and prove the clarity of budget targets, internal control and organizational commitment to budget gaps in the regional services of Jombang Regency, East Java, Indonesia. This research uses a quantitative approach using primary data. The primary data is a questionnaire distributed to respondents. The research sample was taken using a simple random sampling technique and sample determination using the Slovin formula. The data analysis technique used in this research is the SmartPLS Windows 4.0 application software. The research results prove that the variables of clarity of budget targets and organizational commitment have an influence on budget slack. Meanwhile, internal control has no influence on budgetary slack. The implications of the results of this research indicate that to reduce budget gaps, the Jombang Regency regional government needs to focus on increasing the clarity of budget targets and strengthening organizational commitment in budget management. In addition, although internal control was not proven to be influential in this research, it is still important for organizations to continue to improve and monitor internal control systems as part of overall efforts to increase budget efficiency and accountability.